(untitled) (Eurasian Research Bulletin, 2022)
Growing integration of the world’s economies, cultures, and politics generates increasing global communication and with that, unprecedented volumes of materials for translation, in all languages, in all directions. This poses a seemingly impossible challenge, as human translation of such a vast body of texts requires an infinitely large number of skilled translators, and as the number of texts is multiplying by the second, it becomes virtually an unfeasible task to translate all of them. This article deals with the term of cognitive phenomenon in translation and the concept of discourse. The author discusses the cognitive model of translation and also analyzes properties of discursive activity.